Pengaruh Teknologi Terhadap Pendidikan Karakter dan Budaya Bangsa Siswa Sekolah Dasar - Elza Amalia Salsya Bani; Mila Andriani Nurcahya; Moch Lucky Winandar; Yusuf Tri Herlambang (Jurnal Pendidikan Indonesia (JOUPI), 2023)
The very rapid development of technology has an influence on the character education and national culture of elementary school students. This is because the technology used by humans can have both good and bad impacts according to the actions they take. This research aims to explain the impact of technology and learning on character and culture in the learning process of elementary school children. The qualitative method is the method used in this research. The research subjects used by researchers were fifth grade elementary school teachers in Cicalengka subdistrict. The data collection process in this research consisted of stakeholder group interviews. The research results obtained in this study show that technology can influence student behavior and culture. Because during the pandemic, if parents don't look after them and teachers don't improve the learning process, children will become lazy and instead of opening their cellphones to study, they will play with their cellphones.